High dietary arachidonic acid levels induce changes in complex lipids and immune-related eicosanoids and increase levels of oxidised metabolites in zebrafish (Danio rerio). Issue 8 (9th May 2017) - Adam, Anne-Catrin; Lie, Kai K.; Moren, Mari; Skjærven, Kaja H.
Abstract: This study explores the effect of high dietary arachidonic acid (ARA) levels (high ARA) compared with low dietary ARA levels (control) on the general metabolism using zebrafish as the model organism. The fatty acid composition of today's 'modern diet' tends towards higher n- 6 PUFA levels in relation to n -3 PUFA. Low dietary n- 3: n- 6 PUFA ratio is a health concern, as n- 6 PUFA give rise to eicosanoids and PG, which are traditionally considered pro-inflammatory, especially when derived from ARA. Juvenile zebrafish fed a high-ARA diet for 17 d had a lower whole-body n- 3: n- 6 PUFA ratio compared with zebrafish fed a low-ARA (control) diet (0·6 in the control group v . 0·2 in the high-ARA group). Metabolic profiling revealed altered levels of eicosanoids, PUFA, dicarboxylic acids and complex lipids such as glycerophospholipids and lysophospholipids as the most significant differences compared with the control group. ARA-derived hydroxylated eicosanoids, such as hydroxy-eicosatetraenoic acids, were elevated in response to high-ARA feed. In addition, increased levels of oxidised lipids and amino acids indicated an oxidised environment due to n- 6 PUFA excess in the fish. To conclude, our results indicate that an ARA-enriched diet induces changes in complex lipids and immune-related eicosanoids and increases levels of oxidised lipids and amino acids, suggesting oxidative stress and lipid peroxidation.